Result of the species identification of the leaf beetles damaging Cocos nucifera L. and Roystonea regia (H. B. K.) Cook, in the Mekong delta - Niem, Nguyen Xuan; Hue, Le Xuan (Academia Journal of Biology, 2014)
Studying the morphological characteristics of the leaf beetles damaging Cocos nucifera L. and Roystonea regia (H. B. K.) Cook in the Mekong delta, we have noticed that the body sizes of leaf beetles on Roystonea regia were bigger than those of Cocos nucifera. Because their colour, their striato-punctates on antennae, their elytra, their pronotum, their abdomen and their male-female genitalia were not different so we recognized that the leaf beetles on the above mentioned plants were the same species Brontispa longissima (Gestro), 1885 (Coleoptera: Chrysomelidae: Hispinae).